A role of the “world-class” public realm in Cardiff - Kozhakhmetov, Adilet; Inam, Aseem; Abilov, Alexey (project baikal, 2023)
Urbanism principles in the context of the UK have significantly changed its urban public realm since the 1980s to shape a “world-class” public realm by welcoming high-income groups. However, there are still limited investigations into the performative role of the public realm. Therefore, the research aims to ask what the social impact of the equitable public realm is for every citizen. These findings will be archived through morphological mappings, observation, and photographing. While the research confirms that “world-class” public realms in cities are rather exclusive than inclusive, there is a framework for potential urban transformations.